1
$\begingroup$

I'm told to prove this by Mathematical Induction: $ 1\times3 +2\times4 + \cdots + n(n+2) = \frac{1}{6} \times n(n+1)(2n+7)$

This is what I have so far:

BC: Try $n=1$:

$ 1\times3 +2\times4 + \cdots + n(n+2) = \dfrac{1}{6} \times n(n+1)(2n+7)$

$ 3= \dfrac{1}{6} \times 2(9) = 3$

So Base case is true:

IH: Let $n = k$. $ 1\times3 +2\times4 + \cdots + k(k+2) = \frac{1}{6} \times k(k+1)(2k+7)$

IS: show that

$n \implies n+1$

I'm told to only work from one side, so I've attempted the left side (I was told I can't plug this into both sides).

We Have:

$ 1\times3 +2\times4 + \cdots + (k+1)(k+3) = ...$

I'm not sure where to go from here, any help would be greatly appreciated!!

$\endgroup$
  • $\begingroup$ \cdots and \implies ($\cdots$ and $\implies$) might be useful for further questions. $\endgroup$ – JnxF Jan 24 '16 at 0:09
3
$\begingroup$

$$ \begin{align} 1 \times 3+2 \times 4+ \cdots +k(k+2)+(k+1)(k+3) &=\frac{1}{6} \times k(k+1)(2k+7)+(k+1)(k+3) \\[5pt]&=(k+1)\left(\frac{2k^2+7k}{6}+k+3\right) \\[5pt]&=(k+1)\left(\frac{2k^2+7k+6k+18}{6}\right) \\[5pt]&=(k+1)\left(\frac{2k^2+13k+18}{6}\right) \\[5pt]&=\frac{(k+1)(k+2)(2(k+1)+7)}{6} \end{align} $$

$\endgroup$
  • $\begingroup$ And then I plug in the original value for the answer, or can I just leave it be? $\endgroup$ – EDEDE Jan 23 '16 at 23:55
  • $\begingroup$ @EDEDE see edition. $\endgroup$ – Jane Jan 23 '16 at 23:57
  • $\begingroup$ Cheers, thanks! $\endgroup$ – EDEDE Jan 23 '16 at 23:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.